A new 40Ar/39Ar eruption age for the Mount Widderin volcano, Newer Volcanic Province, Australia, with implications for eruption frequency in the region. Issue 2 (17th February 2016) - Matchan, E. L.; Joyce, E. B.; Phillips, D.
ABSTRACT: The Mount Widderin shield volcano is located near Skipton, western Victoria, in the Western Plains subprovince of the monogenetic Pliocene–Holocene Newer Volcanic Province (NVP). Radiometric ages for lavas in the Hamilton–Skipton–Derrinallum area are few, owing to limited suitable outcrop for K–Ar or 40 Ar/ 39 Ar geochronology studies. Existing age constraints for flows in this area have been inferred from Regolith Landform Units (RLUs), complemented by a small number of K–Ar studies on ≥1 Ma flows. Although the RLU approach provides a valuable overview of relative eruption ages across the NVP, it is of limited use in eruption frequency studies. Additional radio-isotopic ages are required to refine age ranges for individual RLUs, and to validate previous assignment of individual flows to specific RLUs. We report a new, high-precision 40 Ar/ 39 Ar age of 389 ± 8 ka (2σ) for a Mount Widderin basalt sample. Based on this age and geomorphic observations, we propose that both the Widderin and Elephant lava flows be reassigned from the Eccles RLU to the Rouse RLU. We use the 389 ± 8 ka (2σ) age for Widderin, along with published K–Ar ages, to anchor a stratigraphic sequence of 15 individual flows in the Hamilton–Skipton–Derrinallum area, demonstrating that intermittent volcanism has occurred in this area from ≥3 Ma to ≤0.389 Ma. Within the limits of available data for the NVP, this time span of volcanic activity is second only to that of the Melbourne area. We consider the significance of the Widderin eruption age, in conjunction with published age constraints for maars and scoria cones of the Western Plains subprovince, building on previous studies that have focused solely on lava flow ages. The inclusion of the additional data weakens the argument for a decrease in volcanic activity after ca 0.9 Ma as implied by published ages for lava flows only. Additional detailed combined geochronology–geomorphology studies of lavas, scoria cones and maars in strategically selected small areas are advocated to better understand eruption frequency across the NVP.